2019
DOI: 10.1039/c8ta10850a
|View full text |Cite
|
Sign up to set email alerts
|

Structural tailoring of hierarchical fibrous composite membranes to balance mass transfer and heat transfer for state-of-the-art desalination performance in membrane distillation

Abstract: Membrane distillation (MD) displays superior characteristics to other technologies to alleviate the ever-increasing freshwater crisis through seawater desalination and/or wastewater recycling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(12 citation statements)
references
References 48 publications
(35 reference statements)
0
11
0
Order By: Relevance
“…[82][83][84] The thickness of membranes also significantly impacts the efficiency of MD because thicker membranes have higher mass transfer resistance, resulting in a lower permeate flux. 85,86 Generally, the vapor flux initially increases with decreasing membrane thickness. However, a thinner membrane also reduces the thermal resistance resulting in a lower interface temperature difference, and the heat loss becomes dominant, which starts declining as a result of conduction losses when thickness goes below an optimal value.…”
Section: Mass and Heat Transfer Managementmentioning
confidence: 99%
See 2 more Smart Citations
“…[82][83][84] The thickness of membranes also significantly impacts the efficiency of MD because thicker membranes have higher mass transfer resistance, resulting in a lower permeate flux. 85,86 Generally, the vapor flux initially increases with decreasing membrane thickness. However, a thinner membrane also reduces the thermal resistance resulting in a lower interface temperature difference, and the heat loss becomes dominant, which starts declining as a result of conduction losses when thickness goes below an optimal value.…”
Section: Mass and Heat Transfer Managementmentioning
confidence: 99%
“…However, a thinner membrane also reduces the thermal resistance resulting in a lower interface temperature difference, and the heat loss becomes dominant, which starts declining as a result of conduction losses when thickness goes below an optimal value. 86,87 Despite that the MD membrane has no strict requirement in mechanical strength, super-thin membranes can be easily destroyed by liquid flow. Thus, the adequate thickness of MD membranes should be strictly controlled to balance between permeate flux, thermal resistance as well as mechanical strength.…”
Section: Mass and Heat Transfer Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, by using the nanofiltration (NF) process, considerable rejection for multivalent salts (such as MgSO 4 ) is expected 6,7 . However, excessive energy consumption and fouling/scaling problems deteriorate separation performance 8,9 . Membrane distillation (MD) has been emerged as a decent thermal‐based desalination process in recent years owing to its attractive characteristics such as the ability to use low‐grade waste heat, employing renewable energy sources like solar, wind, and geothermal energies, treating highly saline brine with lesser dependence on feed concentration and osmotic pressure and so on 10 .…”
Section: Introductionmentioning
confidence: 99%
“…CFMs with a modified structure (TiO 2 [ 32 , 33 ], SiO 2 [ 34 , 35 , 36 ], carbon nanotubes [ 37 , 38 ], and silver nanoparticle [ 39 , 40 ]) can achieve anti-fouling or anti-bacterial performance. The membranes with different pore sizes of PVDF-HFP skin layer and polyethylene terephthalate (PET) supporting layer can increase the membrane strength and enhance the MD performance [ 41 ]. Except for hydrophilic and hydrophobic membranes [ 42 , 43 ], most of the studies on the CFMs are always found in direct contact MD (DCMD) [ 28 , 44 , 45 ].…”
Section: Introductionmentioning
confidence: 99%